Laminate having thermoelectric conversion layer, method for producing same, and power generation module

JP7627940B2Active Publication Date: 2025-02-07NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
JP2021044919
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-18
Publication Date
2025-02-07
Estimated Expiration
2041-03-18

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、柔軟性や薄型の熱電変換モジュールを実現でき、生体安全性の高い材料を使用した熱電変換素子を提供することができる。また本発明によれば、複雑なプロセスを必要とせず、自立性を有する熱電変換素子を製造できる方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627940000004
    Figure 0007627940000004
  • Figure 0007627940000005
    Figure 0007627940000005
  • Figure 0007627940000006
    Figure 0007627940000006
Patent Text Reader

Abstract

To provide a thermoelectric conversion element which can be produced from a material having high biological safety, and which enables the materialization of a flexible and slim thermoelectric conversion module, and provide a method for producing a thermoelectric conversion element having a self-standing property without needing a complicated process.SOLUTION: A thermoelectric conversion element is arranged by laminating a first conductive substrate 1, a thermoelectric conversion oxide layer 2 provided on an upside of the first conductive substrate, and a second conductive substrate 3 on an upside of the thermoelectric conversion oxide layer in this order. In the thermoelectric conversion element, the second conductive substrate is formed so as to have an outer periphery located on or inside an outer periphery of the thermoelectric conversion oxide layer. As to respective areas of the layers, the relation given by the following expressions holds: [Area of the first conductive substrate ]≥[Area of the thermoelectric conversion oxide layer]≥[Area of the second conductive substrate], and [Area of the first conductive substrate]>[Area of the second conductive substrate]. For respective thicknesses of the layers, the relation given by the following equation holds: [Thickness of the thermoelectric conversion oxide layer]:([Thickness of the first conductive substrate]+[Thickness of the second conductive substrate])=1:1 to 1:10.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate having a thermoelectric conversion layer and a manufacturing method thereof, and also to a power generation module using the laminate. [Background technology]

[0002] 2. Description of the Related Art Conventionally, as one of the means for effectively utilizing energy, a system that directly converts thermal energy into electrical energy and vice versa using a thermoelectric conversion module having a thermoelectric effect such as the Seebeck effect or the Peltier effect has been put to practical use. In recent years, such thermoelectric conversion modules have attracted attention as a power source for wearable and flexible devices, and there is a demand not only for improved thermoelectric conversion performance, but also for the adoption of materials that are safer for the environment and human body, for improved module flexibility (flexibility and stretchability), and for thinner modules.

[0003] For example, a thermoelectric conversion module has been disclosed in which tiny thermoelectric element chips are densely mounted on mounting lands (which also serve as connection electrodes) on a thin-film resin substrate, and flexibility of the substrate is ensured between the mounting lands, thereby giving the module flexibility (Patent Document 1). There has also been a proposal for a thermoelectric conversion module using a chip of a thermoelectric conversion material manufactured using a release layer (sacrificial layer) (Patent Document 2). On the other hand, a thermoelectric conversion element has been disclosed in which a thermoelectric conversion layer formed by a coating process that enables thin film formation is used as the thermoelectric conversion element, and a binder is mixed with thermoelectric conversion material powder to form a paste, which is then hardened into a thin film on the top surface of an electrode (Patent Document 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-267316 A [Patent Document 2] International Publication No. 2020 / 045379 [Patent Document 3] JP 2008-270410 A Summary of the Invention [Problem to be solved by the invention]

[0005] In Patent Document 1 and Patent Document 2, a bismuth-tellurium thermoelectric semiconductor material is used as the thermoelectric conversion material in the examples, but the thermoelectric semiconductor material contains tellurium (Te) as a constituent element, which is problematic in terms of toxicity and rarity. In addition, the thermoelectric conversion module disclosed in Patent Document 1 appears to be intended for attachment to a drainage pipe, and the thermoelectric element chip itself is relatively thick, so that for wearable applications, it is desirable to use a material with high biosafety and to further reduce the thickness. Furthermore, in the manufacturing process of Patent Document 2, it is necessary to form a peeling layer that is unnecessary for the thermoelectric conversion module itself, making the manufacturing process complicated. Patent Document 3 uses an oxide thermoelectric semiconductor material as the thermoelectric conversion material. However, oxide thermoelectric semiconductor materials are more fragile than metal-based materials such as the above-mentioned bismuth-tellurium-based thermoelectric semiconductor materials, and it is difficult to obtain a thermoelectric element chip that is self-supporting. For this reason, Patent Document 3 uses an embodiment in which a thin film containing an oxide thermoelectric semiconductor material is formed on an electrode on a substrate of a thermoelectric conversion module, but the thin film itself is not self-supporting and is difficult to handle.

[0006] The present invention aims to provide a thermoelectric conversion element that can be manufactured from materials that are highly safe for the human body and that can realize a flexible and thin thermoelectric conversion module, and also to provide a method for manufacturing an independent thermoelectric conversion element without requiring complicated processes. [Means for solving the problem]

[0007] The present inventors conducted intensive research to solve the above problems, and discovered a manufacturing method that uses a highly safe thermoelectric conversion oxide material as a thermoelectric conversion material and can provide a thermoelectric conversion element that overcomes the brittleness that has been a problem with the material, thereby completing the present invention.

[0008] That is, the present invention provides, as a first aspect, A first conductive substrate; a thermoelectric conversion oxide layer provided on an upper side of a first conductive substrate; a second conductive substrate provided on the upper side of the thermoelectric conversion oxide layer, The outer periphery of the second conductive substrate is formed on or inside the outer periphery of the thermoelectric conversion oxide layer, With respect to the areas of the layers, the relationship: [area of ​​the first conductive substrate] ≧ [area of ​​the thermoelectric conversion oxide layer] ≧ [area of ​​the second conductive substrate] and the relationship: [area of ​​the first conductive substrate] > [area of ​​the second conductive substrate] is satisfied; The present invention relates to a thermoelectric conversion element, characterized in that the thicknesses of the layers satisfy the relationship of [thickness of thermoelectric conversion oxide layer]:〈[thickness of first conductive substrate]+[thickness of second conductive substrate]〉=1:1 to 1:10. As a second aspect, the present invention relates to the thermoelectric conversion element according to the first aspect, in which a first conductive paste layer is formed between a first conductive substrate and a thermoelectric conversion oxide layer, and a second conductive paste layer is formed between the thermoelectric conversion oxide layer and a second conductive substrate. As a third aspect, the thermoelectric conversion oxide layer is 0.5 mm 2 ~20mm 2 The thermoelectric conversion element according to the first or second aspect has an area of As a fourth aspect, the thermoelectric conversion oxide layer is General formula (1): CaMn 1-x M 1 x O y (1) (In the formula, M 1 is at least one element selected from the group consisting of Nb, Ta, Mo and W, and x and y are numbers that satisfy 0≦x≦0.1 and 2.8≦y≦3.2. An n-type thermoelectric conversion layer made of an oxide composite containing a perovskite-type calcium manganese oxide represented by the formula: General formula (2) or general formula (3): Ca 3-p Bi p Co4O q (2) (In the formula, p and q are numbers that satisfy 0≦p≦1 and 8.5≦q≦10.) Bi2Sr 2-r Ca r Co2O t (3) (In the formula, r and t are numbers that satisfy 0.0≦r≦2.0 and 8.5≦t≦10.) A p-type thermoelectric conversion layer made of an oxide composite containing a cobalt-based oxide represented by That is, The present invention relates to a thermoelectric conversion element according to any one of the first to third aspects. As a fifth aspect, there is provided a method for manufacturing a thermoelectric conversion element, comprising: A step of applying a conductive paste onto a first conductive substrate and firing the paste to form a first conductive paste layer; applying a thermoelectric conversion oxide layer-forming composition onto the first conductive paste layer to form a coating; A step of baking the coating at 300° C. or higher to form a thermoelectric conversion oxide layer; Separately, a step of applying a conductive paste onto a second conductive substrate and drying the paste to form a second conductive paste layer; a step of stacking the first conductive substrate and the second conductive substrate such that the thermoelectric conversion oxide layer and the second conductive paste layer face each other, and pressing the resultant in a stacking direction at 300° C. or higher; The present invention relates to a method for manufacturing a thermoelectric conversion element, comprising: As a sixth aspect, there is provided a method for manufacturing a thermoelectric conversion element, comprising the steps of: A step of applying a conductive paste onto a first conductive substrate and firing the paste to form a first conductive paste layer; applying a thermoelectric conversion oxide layer-forming composition onto the first conductive paste layer to form a coating; a step of baking the coating at 300° C. or higher to form a thermoelectric conversion oxide layer 1; Separately, a step of applying a conductive paste onto a second conductive substrate and firing the same to form a second conductive paste layer; applying a thermoelectric conversion oxide layer-forming composition onto the second conductive paste layer to form a coating; a step of baking the coating at 300° C. or higher to form a thermoelectric conversion oxide layer 2; a step of stacking the first conductive substrate and the second conductive substrate such that the thermoelectric conversion oxide layer 1 and the thermoelectric conversion oxide layer 2 face each other, and pressing the resultant in the stacking direction at 300° C. or higher; The present invention relates to a method for manufacturing a thermoelectric conversion element, comprising: As a seventh aspect, a thermoelectric power generation module is provided, which uses a plurality of thermoelectric conversion elements as described in the fourth aspect, and is formed by connecting a plurality of thermoelectric conversion elements in series by a method in which an unjoined end of a p-type thermoelectric conversion element having a p-type thermoelectric conversion layer is connected to an unjoined end of an n-type thermoelectric conversion element having an n-type thermoelectric conversion layer on a substrate. Effect of the Invention

[0009] According to the present invention, it is possible to realize a flexible and thin thermoelectric conversion module, and to provide a thermoelectric conversion element using a material with high biosafety. Furthermore, according to the present invention, it is possible to provide a method for manufacturing a self-supporting thermoelectric conversion element without requiring a complicated process. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 shows an embodiment (a) and (b) of a thermoelectric conversion element of the present invention, and shows cross-sectional views ((a-1) and (b-1)) and top views ((a-2) and (b-2)). [Diagram 2] FIG. 2 is a top view showing the manufacturing procedure of the thermoelectric conversion module produced in Example 3. [Diagram 3] FIG. 3 shows a cross-sectional view of the thermoelectric power generation module produced in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Thermoelectric conversion element] The thermoelectric conversion element (laminate having a thermoelectric conversion layer) of the present invention is a thermoelectric conversion element comprising a first conductive substrate, a thermoelectric conversion oxide layer provided on the upper side of the first conductive substrate, and a second conductive substrate provided on the upper side of the thermoelectric conversion oxide layer, laminated in this order, and the outer periphery of the second conductive substrate is formed on or inside the outer periphery of the thermoelectric conversion oxide layer.

[0012] In the thermoelectric conversion element of the present invention, the areas of the layers satisfy the relationship [area of ​​the first conductive substrate]≧[area of ​​the thermoelectric conversion oxide layer]≧[area of ​​the second conductive substrate] and also the relationship [area of ​​the first conductive substrate]>[area of ​​the second conductive substrate]. In the thermoelectric conversion element having the above-mentioned laminated structure, if the first conductive substrate and the second conductive substrate come into contact (conduct), the element does not function as a thermoelectric conversion element, and therefore such a contact state is not actually included. To avoid such a contact state, the outer periphery of the second conductive substrate is usually formed on or inside the outer periphery of the thermoelectric conversion oxide layer, that is, the second conductive substrate is disposed extending from the inside to the outside of the thermoelectric conversion oxide layer. Also, the outer periphery of the thermoelectric conversion oxide layer can be formed on or inside the outer periphery of the second conductive substrate. For example, in a preferred embodiment, the relationship: [area of ​​the first conductive substrate] ≥ [area of ​​the thermoelectric conversion oxide layer] > [area of ​​the second conductive substrate] is established. That is, as shown in FIG. 1(a), When viewed from a cross section (Figure 1(a-1)), the first conductive substrate 1, thermoelectric oxide layer 2, and second conductive substrate 3 become smaller in size toward the top of the page, and when viewed from above (Figure 1(a-2)), the second conductive substrate 3 is provided without protruding from the thermoelectric conversion oxide layer 2.

[0013] The thermoelectric conversion element of the present invention preferably has an area size as small as possible from the viewpoint of improving the flexibility of a thermoelectric conversion module assembled from the element. For example, the thermoelectric conversion oxide layer is 0.5 mm 2 ~20mm 2The thermoelectric conversion oxide layer can be preferably 1 mm 2 ~10mm 2 , e.g. 2mm 2 ~5mm 2 The size of the slit may be 100 mm.

[0014] Furthermore, in the thermoelectric conversion element of the present invention, the thickness of each of the layers satisfies the relationship of [thickness of thermoelectric conversion oxide layer]:〈[thickness of first conductive substrate]+[thickness of second conductive substrate]〉=1:1 to 1:10. In most of the thermoelectric conversion elements proposed so far, from the viewpoint of thermoelectric conversion efficiency, the thermoelectric conversion layer is usually relatively thick compared to the conductive substrates on both the upper and lower sides. In the thermoelectric conversion element (laminate) of the present invention, from the viewpoint of improving the flexibility of a thermoelectric conversion module assembled from the elements, it is desirable that the overall thickness of the thermoelectric conversion element is as thin as possible within a range that does not impair the independence or thermoelectric conversion capacity of the thermoelectric conversion element itself. For example, if the entire thermoelectric conversion element is thick, when a thermoelectric conversion module in which the element is provided is bent into a curved surface, there is a possibility that the elements will come into contact with each other if the elements are provided on the inside of the curved surface, and there is a risk that the upper electrode (on the outside of the curved surface) connecting the elements will be stretched and broken if the elements are provided on the outside of the curved surface. However, in the thermoelectric conversion element of the present invention, if the thickness of the first conductive substrate and the second conductive substrate is too thin, the element may not be able to maintain its independence because the thermoelectric conversion oxide layer is a relatively fragile layer obtained by sintering an oxide as described below. On the other hand, if the first conductive substrate and the second conductive substrate are made too thick, the thermoelectric conversion module may become excessively hot, the module may become difficult to handle, and the cost may increase. In view of these, the thermoelectric conversion element of the present invention is configured so that the thickness of the thermoelectric conversion layer is approximately equal to or even thinner than the thickness of the conductive substrate located outside it, that is, so that the above-mentioned relationship is established. In a preferred embodiment, the thermoelectric conversion element of the present invention can satisfy the relationship of [thickness of thermoelectric conversion oxide layer]:〈[thickness of first conductive substrate]+[thickness of second conductive substrate]〉=1:2 to 1:5.

[0015] In the thermoelectric conversion element of the present invention, the thickness of each layer constituting the laminate can be set appropriately taking into consideration the above-mentioned factors. For example, the thickness of the thermoelectric conversion layer can be in the range of 50 μm to 200 μm, and the thickness of the entire thermoelectric conversion element can be in the range of 100 μm to 2.2 mm.

[0016] In a preferred embodiment, a first conductive paste layer is provided between the first conductive substrate and the thermoelectric conversion oxide layer, and a second conductive paste layer is provided between the thermoelectric conversion oxide layer and the second conductive substrate. By providing these conductive paste layers, good conductivity can be imparted between the thermoelectric conversion layer and the conductive substrate, and the conductive paste layers act as anchors to improve the bonding (adhesion) between the conductive substrate and the thermoelectric conversion oxide layer. Furthermore, the area of ​​these conductive paste layers satisfies the following relationship: [area of ​​first conductive substrate]≧[first conductive paste layer]≧[area of ​​thermoelectric conversion oxide layer]≧[second conductive paste layer]≧[area of ​​second conductive substrate]. Preferably, the relationship is: [area of ​​first conductive substrate]≧[first conductive paste layer]≧[area of ​​thermoelectric conversion oxide layer]>[second conductive paste layer]≧[area of ​​second conductive substrate] (see FIG. 1(b)). That is, as shown in FIG. 1(b) as an example, when viewed from a cross section (FIG. 1(b-1)), the first conductive substrate 1 has a thickness of 1000 μm. The first conductive paste layer 4, thermoelectric oxide layer 2, second conductive paste layer 5, and second conductive substrate 3 become smaller in size toward the upper side of the paper (second conductive substrate 3), and when viewed from above (Figure 1(n-2)), the second conductive substrate 3 is provided without protruding from the thermoelectric conversion oxide layer 2. Moreover, it is desirable that the conductive paste layer has a thickness that allows it to exert an anchor effect while not preventing an increase in the thickness of the entire element, and the thickness can be, for example, about 1 μm to 50 μm.

[0017] [First conductive substrate, second conductive substrate] The conductive substrates (first and second) are not particularly limited as long as they are made of a material having sufficient electrical conductivity, but a substrate having low electrical resistivity is more preferable in order to increase the output from the thermoelectric conversion module. For example, a substrate made of a sheet-like conductive metal, a conductive ceramic substrate, an insulating ceramic substrate coated with a conductive metal, etc. can be used. Among these, from the viewpoint of flexibility of the thermoelectric conversion module, i.e., making the thermoelectric conversion element itself thinner and making the substrate itself flexible and less likely to crack, sheet-shaped conductive metals can be preferably used as the conductive substrate material.

[0018] The conductive metal may be any metal that does not oxidize or melt at the operating temperature of the thermoelectric conversion module, and examples of such conductive metals include precious metals such as silver, gold, platinum, and palladium, precious metal alloys containing about 30% by mass or more, preferably about 70% by mass or more, of these precious metals, and base metals such as copper, iron, titanium, and aluminum. Specific examples of the sheet-like conductive metal include copper foil, silver foil, gold foil, and iron foil. Among these, silver foil (silver sheet) is preferably used from the viewpoints of price, electrical resistivity, thermal conductivity, and the like, and for example, silver foil having a thickness of about 50 μm to 1 mm can be preferably used.

[0019] [Thermoelectric conversion oxide layer] In the present invention, the material constituting the thermoelectric conversion oxide layer can be any oxide known as a thermoelectric conversion material, so long as it can be dispersed in a thermoelectric conversion oxide layer-forming composition described below and applied to form a layer. From another perspective, manganese-based oxides and cobalt-based oxides having a Seebeck coefficient of -50 μV / K or more at 100° C. can also be said to be thermoelectric conversion materials, and these known oxides can be used as starting materials. In the thermoelectric conversion oxide layer, the crystallinity of the oxide is not limited. In order to obtain good properties as a thermoelectric conversion layer, it is preferable that the oxide is crystalline, but even if the starting material is amorphous, for example, a thermoelectric conversion oxide layer having good properties can be obtained by applying the thermoelectric conversion oxide layer forming composition to a substrate and then baking it for crystallization. Furthermore, even if the starting material, for example, a manganese-based oxide or a cobalt-based oxide, contains carbon components remaining during the manufacturing process, if the carbon components can be decomposed by the firing process described below, a thermoelectric conversion oxide layer with good thermoelectric properties can be obtained. Similarly, oxygen atoms of manganese-based oxides or cobalt-based oxides can be introduced in a firing step after coating, so that manganese-based oxides or cobalt-based oxides with a lower oxygen atom content than the stoichiometric ratio can also be used as starting materials. In other words, as described below, as long as sufficient properties as a thermoelectric conversion layer can be obtained by applying the thermoelectric conversion oxide layer-forming composition of the present invention to a substrate and then subjecting it to an appropriate firing treatment, the oxide used as the starting material does not need to have sufficient thermoelectric conversion properties. The thermoelectric conversion layer can be an n-type thermoelectric conversion layer made of an oxide complex containing a perovskite-type calcium manganese oxide represented by the general formula (1) described below, or a p-type thermoelectric conversion layer made of an oxide complex containing a cobalt-based oxide represented by the general formula (2) or (3) described below.

[0020] <Perovskite-type calcium manganese oxide> CaMn 1-x M 1 x O y (1) (In the formula, M 1 is at least one element selected from the group consisting of Nb, Ta, Mo and W, and x and y are numbers that satisfy 0≦x≦0.1 and 2.8≦y≦3.2. Particularly preferred perovskite-type calcium manganese oxides represented by general formula (1) are shown in Table 1. [Table 1]

[0021] <Cobalt-based oxide> Ca 3-p Bi p Co4O q (2) (In the formula, p and q are numbers that satisfy 0≦p≦1 and 8.5≦q≦10.) Bi2Sr 2-r Ca r Co2O t (3) (In the formula, r and t are numbers that satisfy 0.0≦r≦2.0 and 8.5≦t≦10.) Particularly preferred cobalt-based oxides represented by general formula (2) or formula (3) are shown in Table 2. [Table 2]

[0022] [Conductive paste layer] The conductive paste layer is a layer formed from a conductive paste. The conductive paste layer acts as an adhesive for joining the thermoelectric conversion layer to the conductive substrate, and is formed from a conductive paste containing a conductive metal including one or a mixture of two or more precious metals such as silver, gold, platinum, palladium, etc. The conductive metal is usually blended in the conductive paste in the form of a powder. The particle size of the metal powder is not particularly limited, but usually, a powder having a particle size in which the 50% average particle size in the particle size distribution is in the range of about 0.05 to 50 μm can be used.

[0023] [Method of manufacturing thermoelectric conversion element] The thermoelectric conversion element of the present invention, for example, a thermoelectric conversion element having a conductive paste layer, can be manufactured by the following steps (1-1) to (1-5). In an embodiment not having a conductive paste layer, steps (1-1) and (1-4) can be omitted, and the first conductive paste layer in step (1-2) can be read as a first conductive substrate, and the second conductive paste layer in step (1-5) can be read as a second conductive substrate. (1-1) a step of applying a conductive paste onto a first conductive substrate and firing the paste to form a first conductive paste layer; (1-2) applying a thermoelectric conversion oxide layer-forming composition onto the first conductive paste layer to form a coating; (1-3) firing the coating at 300° C. or higher to form a thermoelectric conversion oxide layer; (1-4) separately applying a conductive paste onto a second conductive substrate and drying the paste to form a second conductive paste layer; (1-5) A process of stacking the first conductive substrate and the second conductive substrate so that the thermoelectric conversion oxide layer and the second conductive paste layer face each other, and pressing them in the stacking direction at 300°C or higher.

[0024] In another embodiment, the thermoelectric conversion element of the present invention including a conductive paste layer can be produced by the following steps (2-1) to (2-7). In an embodiment that does not include a conductive paste layer, steps (2-1) and (2-4) can be omitted, and the first conductive paste layer in step (2-2) can be read as a first conductive substrate, and the second conductive paste layer in step (2-5) can be read as a second conductive substrate. (2-1) applying a conductive paste onto a first conductive substrate and firing the paste to form a first conductive paste layer; (2-2) applying a thermoelectric conversion oxide layer-forming composition onto the first conductive paste layer to form a coating; (2-3) firing the coating at 300° C. or higher to form a thermoelectric conversion oxide layer 1; (2-4) separately applying a conductive paste onto a second conductive substrate and firing the same to form a second conductive paste layer; (2-5) applying a thermoelectric conversion oxide layer-forming composition onto the second conductive paste layer to form a coating; (2-6) firing the coating at 300° C. or higher to form a thermoelectric conversion oxide layer 2; (2-7) A process of stacking the first conductive substrate and the second conductive substrate so that thermoelectric conversion oxide layer 1 and thermoelectric conversion oxide layer 2 face each other, and pressing them in the stacking direction at 300°C or higher. The above steps (2-1) to (2-3) and steps (2-4) to (2-6) can be carried out in accordance with the above steps (1-1) to (1-3), and step (2-7) can be carried out in accordance with the above step (1-5).

[0025] (1-1) A step of applying a conductive paste onto a first conductive substrate and firing the paste to form a first conductive paste layer: In this step, first, the conductive paste is applied onto the conductive substrate by screen printing or the like. After application, the solvent contained in the conductive paste is dried, for example, at about 100° C., and then the conductive paste is fired as necessary. The firing temperature is not particularly limited, but firing at a temperature of, for example, about 500 to 900° C. can strengthen the bond with the conductive substrate and form a layer that has an anchor effect for the thermoelectric conversion oxide layer described later.

[0026] (1-2) applying a thermoelectric conversion oxide layer-forming composition onto the first conductive paste layer to form a coating; The thermoelectric conversion oxide layer forming composition used in this step contains the above-mentioned thermoelectric conversion material, i.e., perovskite-type calcium manganese oxide or cobalt oxide, and a dispersion medium. The method for preparing the thermoelectric conversion layer forming composition is not particularly limited, and the above-mentioned oxide, dispersion medium, etc. may be added in appropriate amounts to a reaction (mixing) vessel and mixed, and wet grinding, ball milling, etc. may be performed as necessary. If necessary, the composition may contain a polysaccharide such as ethyl cellulose for the purpose of improving the dispersibility and coating property of the oxide, and may also contain a conductive paste as a conductive auxiliary.

[0027] In the present invention, in order to disperse the above oxides (perovskite-type calcium manganese oxide, cobalt oxide) in a dispersion medium, the oxides are desirably in the form of particles, and it is preferable to use oxides having an average particle size of about 1 nm to 100 μm, since this makes it easy to prepare a uniform dispersion (composition for forming a thermoelectric conversion oxide layer). If the particle size is less than 100 μm, the particles will aggregate and become difficult to disperse, and if it is more than 100 μm, not only will the dispersibility be poor, but there is also a risk that a uniform thermoelectric conversion oxide layer cannot be formed. From the viewpoint of the coatability of the dispersion (composition) and the thermoelectric properties of the thermoelectric conversion oxide layer, the average particle size is preferably 5 μm or less, and more preferably 1 μm or less. Here, the average particle size is determined as the 50% average particle size based on the particle size distribution. The average particle size of the oxide as the starting material may be 1 nm or more. Even if the particle size of the starting material is 100 μm or more, it is sufficient to mix the starting material with a dispersion medium or the like, and then pulverize the particles by wet pulverization, ball milling, or the like to obtain an oxide with a particle size that can be dispersed in the dispersion medium.

[0028] As the dispersion medium, an organic solvent or water having insulating properties is preferably used. Examples of the organic solvent include alcohols such as terpineol (main component is α-terpineol), phenoxyethanol, and the like, aliphatic halogen-based solvents such as chloroform, aprotic polar solvents such as N,N-dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), and dimethylsulfoxide (DMSO), and the like, aromatic solvents such as chlorobenzene, dichlorobenzene, benzene, toluene, xylene, mesitylene, tetralin, tetramethylbenzene, and pyridine, ketone-based solvents such as cyclohexanone, acetone, and methyl ethyl ketone, ether-based solvents such as diethyl ether, tetrahydrofuran (THF), t-butyl methyl ether, dimethoxyethane, and diglyme, and hydrocarbon-based solvents such as decane, undecane, dodecane, tridecane, and tetradecane. Among these organic solvents, one type can be used alone, or two or more types can be used in combination.

[0029] In the thermoelectric conversion oxide layer-forming composition, the blending amount (mass %) of the oxide (perovskite-type calcium manganese oxide, cobalt oxide) can be, for example, 0.1 to 90 mass %. If the oxide concentration is too high, the composition does not have fluidity, making it difficult to obtain a thermoelectric conversion oxide layer by a coating method. On the other hand, if the solid content concentration is too low, the composition does not provide a uniform film. When the conductive paste is blended as the conductive auxiliary, the blending amount can be 10 to 30 mass % relative to the thermoelectric conversion oxide layer forming composition.

[0030] The method and apparatus for applying the composition onto a conductive paste layer (or onto a conductive substrate) to obtain a coating are not particularly limited. For example, a coating method such as spin coating, blade coating, bar coating, roll coating, curtain coating, spray coating, dip coating, screen printing, etc. can be used, and known apparatuses can be used for these methods.

[0031] (1-3) A step of firing the coating at 300° C. or higher to form a thermoelectric conversion oxide layer. In this step, the coating obtained in the previous step is fired to sinter the oxides (perovskite-type calcium manganese oxide, cobalt oxide) to obtain a thermoelectric conversion oxide layer. The firing of the coating can be carried out at a temperature and time suitable for the purpose of removing and decomposing components that are not involved in the thermoelectric properties, such as the dispersion medium and polysaccharides, and components that may adversely affect the thermoelectric properties, such as carbon components, crystallizing the oxide, and sintering the oxide. For example, the firing can be carried out in an oxidizing atmosphere at 300°C or higher. However, if the firing temperature is too high, the perovskite-type calcium manganese oxide or cobalt-based oxide will undergo a phase transition and the thermoelectric properties will change, so the upper limit of the firing temperature is limited by the phase transition temperature of the oxide. For example, CaMn 0.98 Mo 0.02When using O3, the thermoelectric properties change when fired at 1300°C or higher, so the firing temperature is preferably 1300°C or lower. When using Ca3Co4O9 as the cobalt-based oxide, it has a phase transition temperature of 860°C, so the firing temperature is preferably 850°C or lower. The firing can be performed by heating in an oven or by light firing (light sintering) using ultraviolet light, visible light, flash light, or other light irradiation. In addition, the firing can be performed by combining heating and light firing. It is also possible.

[0032] (1-4) Separately, a step of applying a conductive paste onto a second conductive substrate and drying the paste to form a second conductive paste layer. This step can be carried out in the same manner as the above-mentioned step (1-1), except that after the conductive paste is applied onto the conductive substrate and dried, firing is not carried out.

[0033] (1-5) A step of stacking the first conductive substrate and the second conductive substrate so that the thermoelectric conversion oxide layer and the second conductive paste layer face each other, and pressing the resultant in the stacking direction at 300° C. or higher. In this step, the substrate (first conductive substrate-first conductive paste layer-thermoelectric conversion oxide layer) obtained in steps (1-1) to (1-3) and the substrate (second conductive substrate-second conductive paste layer) obtained in step (1-4) are stacked so that the conductive substrates face outward and the thermoelectric conversion oxide layer and the second conductive paste layer face each other, and then the stack is pressed under pressure in the stacking direction (perpendicular to the bonding surface). After pressing under pressure, the thermoelectric conversion oxide layer and the second conductive paste layer are bonded to obtain a thermoelectric conversion element, which is a laminate. The pressure pressing can be performed at a pressure that does not damage or deform the thermoelectric conversion layer, the conductive substrate, etc., such as 1 to 20 MPa and a temperature of about 500 to 1000°C.

[0034] According to the manufacturing method of the present invention, a first conductive paste layer and a thermoelectric conversion oxide layer of approximately the same size are formed on a first conductive substrate, while a second conductive substrate smaller in size than the first conductive substrate (for example, 1 / 3 to 1 / 10 the size of the first conductive substrate) is adopted, and when these are opposed to each other, a plurality of second conductive substrates (on which a second conductive paste layer is formed) can be arranged at appropriate intervals on the thermoelectric conversion oxide layer (on the first conductive substrate). After pressing, the thermoelectric conversion oxide layer portion exposed between one second conductive substrate and another second conductive substrate is cut in the stacking direction (thermoelectric conversion oxide layer-first conductive paste layer-first conductive substrate), thereby making it possible to obtain a plurality of thermoelectric conversion elements.

[0035] The thermoelectric conversion element of the present invention is an element having an n-type thermoelectric conversion layer made of an oxide complex containing a perovskite-type calcium manganese oxide as a thermoelectric conversion oxide layer (hereinafter referred to as n-type thermoelectric conversion element), and an element having a p-type thermoelectric conversion layer made of an oxide complex containing a cobalt-based oxide (hereinafter referred to as p-type thermoelectric conversion element), which are arranged in parallel in the direction of temperature difference, and a plurality of thermoelectric conversion elements are electrically connected in series by connecting wiring above and below these n-type / p-type thermoelectric conversion elements, and a lead wire or the like is drawn from the end of the series connection, thereby making it possible to create a thermoelectric conversion module (also referred to as a thermoelectric power generation module). EXAMPLES

[0036] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following description.

[0037] [Ca 2.7 Bi 0.3 Production of Co4O9 powder] Ca used in this example 2.7 Bi 0.3 The Co4O9 powder was synthesized as follows with reference to JP-A-2003-246678. First, calcium carbonate (CaCO3), bismuth oxide (Bi2O3) and cobalt oxide (Co3O4) were weighed out to a stoichiometric ratio (Ca:Bi:Co=2.7:0.3:4) and mixed in a mortar. The mixed sample was then placed in an alumina crucible and fired in air at 800°C for 10 hours, and the fired material obtained was thoroughly mixed using an agate mortar and pestle to obtain a powder. This powder was press-molded into a disk shape with a diameter of about 20 mm and a thickness of 2 to 10 mm to obtain a molded body. A gold sheet was laid in an alumina boat, and the molded body was placed on top of it and heated in air at 880°C for 10 hours. The resulting sintered body was sintered for 20 hours. The sintered body was then crushed using an agate mortar and pestle, and the Ca that had passed through the metal sieve was separated using a metal sieve with a mesh size of 38 μm. 2.7 Bi 0.3 Co4O9 powder was obtained.

[0038] [CaMn 0.98 Mo 0.02 Production of O3 powder] The CaMn used in this example 0.98 Mo 0.02 The O3 powder was synthesized as follows, with reference to the contents disclosed in JP 2009-117449 A. First, calcium carbonate (CaCO3), manganese oxide (Mn2O3), and molybdenum oxide (MoO3) were weighed out to a stoichiometric ratio (Ca:Mn:Mo=1:0.98:0.02) and mixed in a mortar. Next, the mixed sample was placed in an alumina crucible and calcined in air at 1000°C for 15 hours, and the calcined product was crushed and mixed in a mortar to obtain a powder. The powder obtained was pressure-molded into a disk shape with a diameter of about 20 mm and a thickness of 2 to 10 mm to obtain a green body. A gold sheet was placed in an alumina boat, and the green body was placed on top of it and sintered in air at 1250°C for 12 hours. This operation was repeated twice to obtain a single-phase CaMn sintered body. 0.98 Mo 0.02 The sintered body was then crushed using an agate mortar and pestle, and the CaMnO3 particles that had passed through a metal sieve with 38 μm openings were sieved. 0.98 Mo 0.02 O3 powder was obtained.

[0039] The Ca3Co4O9 powder used in this example has a BET specific surface area of ​​70 m when measured using a Macsorb HM model-1208 manufactured by Mountec Co., Ltd. 2 / g Ca3Co4O9 was used.

[0040] [Preparation Example 1: Preparation of Thermoelectric Conversion Layer Forming Solution 1 (1)] Ca 2.7 Bi 0.3 Co4O9 powder (8 g, 100 parts by mass), Ca3Co4O9 powder (2 g, 25 parts by mass), and α-terpineol (8 g, 100 parts by mass) were placed in a bottle and mixed 10 times at 2,000 rpm for 4 minutes using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro) to obtain thermoelectric conversion layer forming liquid 1 (composition C).

[0041] [Preparation Example 2: Preparation of thermoelectric conversion layer forming solution 2 (2)] CaMn 0.98 Mo 0.02 O3 powder (8 g, 100 parts by mass), silver paste (manufactured by Tanaka Kikinzoku Kogyo K.K., product name: MH-108A-10) (2 g, 25 parts by mass), and α-terpineol (8 g, 100 parts by mass) were placed in a bottle and mixed ten times at 2,000 rpm for four minutes using a planetary centrifugal mixer (manufactured by Thinky Corporation, Awatori Rentaro) to obtain thermoelectric conversion layer forming liquid 2 (composition M).

[0042] [Example 1: Preparation of thermoelectric conversion element 1 (p-type thermoelectric conversion element) (1)] Silver paste (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., product name: MH-108A-10) was applied by screen printing onto silver foil 1 (thickness 50 μm, size 20 mm x 20 mm) and fired at 860°C to obtain silver paste layer 1. Thermoelectric conversion layer forming liquid 1 (composition C) was then applied on top of that to a thickness of 200 μm and fired at 850°C to obtain a thermoelectric conversion layer. Separately, silver paste (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., product name: MH-108A-10) was applied by screen printing onto 64 sheets of silver foil 2 (thickness 100 μm, size 2 mm × 2 mm) and dried at 100°C to obtain a silver paste layer 2. Next, these 64 pieces of silver foil 2 are arranged vertically and horizontally with equal gaps of 0.5 mm between them, so that 8 pieces are arranged vertically and horizontally. The silver foil 1 is stacked so that the thermoelectric conversion layer of the silver foil 1 faces the silver paste layer 2 of the silver foil 2. The stack is then pressed at 950°C in the stacking direction (30 kgf / cm 2 The thermoelectric conversion layer was firmly bonded to the silver foil 2 via the silver paste layer 2, and a sheet of a thin-flak-like laminate was obtained. Finally, a cutting blade is passed through the gaps (0.5 mm) between the eight pieces of silver foil 2 arranged vertically and horizontally in the laminate, and the laminate is cut into small pieces each having a size of about 2.1 to 2.2 mm x 2.1 to 2.2 mm. Thermoelectric conversion elements 1 (64 pieces) were obtained in which the two silver foils were different in size (area: silver foil 1>silver foil 2). No cracks or peeling were observed in the obtained thermoelectric conversion elements 1.

[0043] [Example 2: Preparation of thermoelectric conversion element 2 (n-type thermoelectric conversion element) (2)] Except for using thermoelectric conversion layer forming liquid 2 (composition M) instead of thermoelectric conversion layer forming liquid 1 (composition C), a thermoelectric conversion element 2 was produced in the same manner as in Example 1. No cracks or peeling were observed in the thermoelectric conversion element 2.

[0044] [Comparative Example 1] Silver paste (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., product name: MH-108A-10) was applied by screen printing onto silver foil H1 (thickness 200 μm, size 20 mm x 20 mm) and fired at 860°C to obtain a silver paste layer H1-1. Thermoelectric conversion layer forming liquid 1 (composition C) was then applied on top of the silver foil H1 (thickness 200 μm, size 20 mm x 20 mm) and fired at 850°C to obtain a thermoelectric conversion layer H1-1. Separately, silver paste (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., product name: MH-108A-10) was applied by screen printing onto silver foil H2 (thickness 200 μm, size 20 mm x 20 mm) and fired at 860°C to obtain a silver paste layer H1-2. Thermoelectric conversion layer forming liquid 1 (composition C) was then applied onto the silver paste layer to a thickness of 200 μm and fired at 850°C to obtain a thermoelectric conversion layer H1-2. The silver foil 1 and the silver foil 2 are stacked so that the thermoelectric conversion layer H1-1 and the thermoelectric conversion layer H1-2 face each other, heated at 450°C, and organic components are removed. Then, the laminate is pressed in the stacking direction at 930°C under pressure (30 kgf / cm 2 The thermoelectric conversion layer H1-1 and the thermoelectric conversion layer H1-2 were firmly bonded to each other, and a single thin-sheet laminate was obtained. Finally, when an attempt was made to cut the laminate into small pieces measuring 2.0 mm × 2.0 mm using a cutter, the silver foil on the side where the blade touched peeled off from the thermoelectric conversion layer due to the impact of the cutting, and it was not possible to obtain a small element that maintained the laminate.

[0045] [Comparative Example 2] Silver paste (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., product name: MH-108A-10) was applied by screen printing onto a PET sheet (thickness 220 μm, size 4 mm x 7 mm) and dried at 100°C to obtain a silver paste layer H2-1. Thermoelectric conversion layer forming liquid 1 (composition C) was then applied on top of the silver paste layer to a thickness of 200 μm and fired at 850°C to obtain a thermoelectric conversion layer H2. Next, a silver paste (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., product name: MH-108A-10) was applied onto the thermoelectric conversion layer by screen printing (conditions) and dried at 100° C. to obtain a silver paste layer H2-2. Finally, the sheet is pressed in the lamination direction at 950°C (30 kgf / cm 2 After pressing, a thin piece was obtained in which a silver film was formed on both sides of the thermoelectric conversion layer H2, but when lifted up, it collapsed, and a free-standing element was not obtained.

[0046] [Resistance measurement] The resistance values ​​of thermoelectric conversion element 1 and thermoelectric conversion element 2 obtained by the above-mentioned procedure were measured, and both showed a value of about 0.8 Ω. The resistance was measured by a direct current four-terminal method. Platinum wires were connected to the surfaces of Silver Foil 1 and Silver Foil 2 using silver paste, and each platinum wire was connected to an ammeter and a voltmeter. A current of 1 mA or 10 mA was applied, the voltage was calculated, and the slope of the current (horizontal axis) - voltage (vertical axis) line was taken as the electrical resistance.

[0047] [Example 3: Fabrication of a thermoelectric conversion module (thermoelectric power generation module)] Using the thermoelectric conversion element 1 (p-type thermoelectric conversion element) obtained in Example 1 and the thermoelectric conversion element 2 (n-type thermoelectric conversion element) obtained in Example 2, a thermoelectric conversion module was produced. First, a 34mm x 38mm square Kapton (polyethylene glycol) sheet with a thickness of 65μm was Fifty silver sheets 1, each measuring 2 mm × 5 mm and 100 μm thick, were arranged on a mid-film with a gap of 1.5 mm between them and then fixed in place using adhesive (Figure 2(A)). Conductive silver paste (die bonding paste, product name: DBC130SD) was applied from both ends of each silver sheet 1 to about 2 mm inside. A total of 50 thermoelectric conversion elements 1 (p-type elements in the figure) of Example 1 and thermoelectric conversion elements 2 (n-type elements in the figure) of Example 2 were placed alternately on the silver paste, and heated at 180°C for 20 minutes in air to solidify the silver paste. At this time, the silver foil 1 side with the larger area of ​​each thermoelectric conversion element was bonded to the silver paste (FIG. 2(B)). Next, conductive silver paste (die bonding paste, product name: DBC130SD) was applied onto the small-area silver foil 2 of each thermoelectric conversion element so as not to protrude from the silver foil. A silver sheet 2 measuring 5 mm in length, 1 mm in width, and 100 μm in thickness was placed on top of the silver paste so as to connect adjacent thermoelectric conversion elements 1 and 2 that were not connected by the silver sheet 1. In this way, 50 pairs of thermoelectric conversion elements were connected in series, and silver sheets 3 measuring 80 mm in length were connected to the thermoelectric conversion elements at both ends to serve as power extraction wires (FIG. 2(C)). Finally, the silver paste was solidified by heating in air at 180°C for 20 minutes using a hot plate to produce a thermoelectric module consisting of 50 pairs of p-type thermoelectric elements and n-type thermoelectric elements. A cross-sectional view of the obtained thermoelectric module is shown in Figure 3. The obtained thermoelectric module was flexible.

[0048] The power output of the thermoelectric conversion module was measured by a four-terminal method. One pair of terminals was connected to a DC ammeter, and the current output by the thermoelectric conversion module was measured while varying the external load. At the same time, the voltage was measured by another pair of terminals connected to a voltmeter. The Kapton side of the thermoelectric conversion module was heated with a hot plate, and a thermally conductive, electrically insulating film was placed on the opposite side, with an aluminum heat dissipation fin placed on top of that, creating a temperature difference in the thermoelectric conversion element. An external resistance was connected to the output wire of the thermoelectric conversion module (Figure 2(C) and Figure 3: silver sheet 3), and the voltage and current were measured while changing the resistance value, and the maximum power generation output was obtained from the voltage x current. Table 3 shows the surface temperature of the hot plate and the power generation output results.

[0049] [Table 3]

[0050] As shown in Table 3, it was confirmed that the thermoelectric conversion module prepared using the thermoelectric conversion elements of the present invention (p-type thermoelectric conversion element, n-type thermoelectric conversion element) has thermoelectric conversion ability, and the maximum power generation output increased as the amount of thermal energy (surface temperature of the hot plate) increased.

Claims

1. a first sheet of conductive metal; a thermoelectric conversion oxide layer disposed on the first sheet of conductive metal; a second sheet-shaped conductive metal provided on the upper side of the thermoelectric conversion oxide layer; and a first conductive paste layer is formed between the first sheet-like conductive metal and the thermoelectric conversion oxide layer, and a second conductive paste layer is formed between the thermoelectric conversion oxide layer and the second sheet-like conductive metal; The outer periphery of the second sheet-shaped conductive metal is formed on the outer periphery of the thermoelectric conversion oxide layer or inside the outer periphery, the areas of the first sheet-shaped conductive metal, the thermoelectric conversion oxide layer, and the second sheet-shaped conductive metal satisfy the relationship: [area of ​​the first sheet-shaped conductive metal] ≧ [area of ​​the thermoelectric conversion oxide layer] ≧ [area of ​​the second sheet-shaped conductive metal], and [area of ​​the first sheet-shaped conductive metal] > [area of ​​the second sheet-shaped conductive metal]; A thermoelectric conversion element, characterized in that the thicknesses of the first sheet-like conductive metal, the thermoelectric conversion oxide layer, and the second sheet-like conductive metal satisfy the relationship: [thickness of thermoelectric conversion oxide layer]: <[thickness of first sheet-like conductive metal] + [thickness of second sheet-like conductive metal]> = 1:1 to 1:

10.

2. The thermoelectric conversion oxide layer is 0.5 mm 2 ~20mm 2 having an area of The thermoelectric conversion element according to claim 1 .

3. The thermoelectric conversion oxide layer is An n-type thermoelectric conversion layer made of an oxide composite containing at least one perovskite-type calcium manganese oxide selected from CaMnO 3 and CaMn 0.98 Mo 0.02 O 3 , or A p-type thermoelectric conversion layer made of an oxide composite containing at least one cobalt-based oxide selected from Ca 3 Co 4 O 9 , Ca 2.7 Bi 0.3 Co 4 O 9 and Bi 2 Sr 2 Co 2 O 9 That is, The thermoelectric conversion element according to claim 1 or 2.

4. A method for manufacturing a thermoelectric conversion element according to claim 1, comprising: applying a conductive paste onto a first sheet-like conductive metal and firing the conductive paste to form a first conductive paste layer; a step of applying a thermoelectric conversion oxide layer-forming composition onto the first conductive paste layer to form a coating; A step of baking the coating at 300° C. or higher to form a thermoelectric conversion oxide layer; Separately, a step of applying a conductive paste onto a second sheet-like conductive metal and drying the conductive paste to form a second conductive paste layer; a step of stacking the first sheet-like conductive metal and the second sheet-like conductive metal such that the thermoelectric conversion oxide layer and the second conductive paste layer face each other, and pressing the stacked layers together at 300° C. or higher in the stacking direction; A method for manufacturing a thermoelectric conversion element, comprising:

5. A thermoelectric power generation module comprising a plurality of thermoelectric conversion elements as described in claim 3, connected in series by a method in which an unjoined end of a p-type thermoelectric conversion element having a p-type thermoelectric conversion layer is connected on a substrate to an unjoined end of an n-type thermoelectric conversion element having an n-type thermoelectric conversion layer.

Citation Information

Patent Citations

  • Heat adjustment device

    EP1737052A1

  • Manufacture of thermoelectric element

    JP1999274579A

  • Thermoelectric module

    JP2002084005A

  • Thermoelectric element and thermoelectric generating module

    JP2002232023A

  • Thermoelectric transducer, thermoelectric transducing module, and method for manufacturing the module

    JP2008270410A